Accuracy of serum IgE concentrations and papule diameter in the diagnosis of cow's milk allergy - Jackeline M. Franco; Ana Paula S.G. Pinheiro; Sarah C.F. Vieira; Íkaro Daniel C. Barreto; Ricardo Q. Gurgel; Renata R. Cocco; Dirceu Solé (Brazilian Society of Pediatrics, 2018)
Objective: To compare serum concentrations of specific IgE and mean papule diameters induced in the immediate skin reactivity test with cow's milk and its fractions with results of the oral challenge test, and to establish cutoff points capable of predicting clinical reactivity to cow's milk in patients treated at a referral service. Methods: One hundred and twenty‐two children (median of 17 months) with a history of immediate reactions to cow's milk and presence of specific IgE for cow's milk and/or its fractions (positive skin and/or IgE serum tests) were submitted to open oral challenge test with cow's milk. Results: The oral challenge test was positive in 59.8% of the children, 49% of whom were males. Serum levels of specific IgE, as well as mean cow's milk papule diameters, were significantly higher in allergic patients (medians: 3.39 kUA/L vs. 1.16 kUA/L, 2.5 mm vs. 0 mm). The optimal cutoff points (Youden's index) of serum IgE specific for cow's milk and its fractions capable of predicting cow's milk reactivity (positive oral challenge test) were: 5.17 kUA/L for cow's milk, 0.95 kUA/L for α‐lactalbumin, 0.82 kUA/L for β‐lactoglobulin, and 0.72 kUA/L for casein, whereas for papule diameters the cutoff points were 3.5 mm for cow's milk and 6.5 mm, 9.0 mm, and 3.0 mm for the α‐lactalbumin, β‐lactoglobulin, and casein fractions, respectively. Conclusions: The cutoff points capable of predicting clinical reactivity to cow's milk were: 5.17 kUA/L for serum‐specific IgE and 3.5 mm for papule diameter measurement, values considered discriminatory for the diagnosis of cow's milk allergy. Resumo: Objetivo: Comparar concentrações séricas de IgE específica e diâmetros médios das pápulas induzidas no teste cutâneo de leitura imediata com leite de vaca e suas frações com resultados do teste de provocação oral e estabelecer pontos de corte, capazes de predizer reatividade clínica ao leite de vaca em pacientes atendidos em um serviço de referência. Métodos: Cento e vinte e duas crianças (mediana 17 meses), com história de reações imediatas ao leite de vaca e presença de IgE específicas para leite de vaca e/ou frações (testes cutâneos e/ou IgE sérica positivos) foram submetidas ao teste de provocação oral aberto com leite de vaca. Resultados: O teste de provocac¸ão oral foi positivo em 59,8% das crianças, 49% eram do sexo masculino. Os níveis séricos de IgE específica, assim como os diâmetros médios das pápulas para leite de vaca, foram significantemente maiores nos alérgicos (medianas: 3,39kUA/L vs. 1,16 kUA/L; 2,5 mm vs. 0 mm). Os "pontos de corte ótimos" (Índice de Youden) das IgE séricas específicas para o leite de vaca e suas frações capazes de predizer a reatividade ao leite de vaca (teste de provocação oral positivo) foram: 5,17kUA/L para o leite de vaca, 0,95 kUA/L para α‐lactoalbumina, 0,82kUA/L para β‐lactoglobulina e 0,72kUA/L para caseína e para os diâmetros de pápulas foram 3,5 mm para leite de vaca e 6,5 mm, 9,0 mm e 3,0 mm para as frações α‐lactoalbumina, β‐lactoglobulina e caseína, respectivamente. Conclusões: Os níveis de corte capazes de predizer reatividade clínica ao leite de vaca foram: 5,17kUA/L para IgE sérica específica e 3,5 mm para a medida do diâmetro da pápula, valores considerados discriminatórios para o diagnóstico da alergia ao leite de vaca. Keywords: Milk hypersensitivity, Accuracy, Child, Epidemiology, ROC curve, Palavras‐chave: Hipersensibilidade a leite, Acurácia, Criança, Epidemiologia, Curva ROC